A Cross-Sectional Study of Diet and Compliance to the Mediterranean Food Regimen Among the People of North Eastern Morocco - Mharchi Saliha; Mechkirrou Latifa; Slamini Maryam; Belasri Lamiaa; El Monhim Bilal; Arabi Mourad (E3S Web of Conferences)
Unhealthy eating habits are the main cause of the emergence of chronic diseases (CD), especially T2D and hypertension. Previous research confirms that the Mediterranean diet (MD) is one of the most balanced diets available, significantly reducing the risk of CD and improving longevity. Our aim is to identify the components of the MD in an adult population of the eastern region (Berkane and Nador), and to measure the degree of compliance to the MD in this community. A food frequency and MD adherence level analysis questionnaire was used. Our sample comprised 800 consultants, with women for the largest proportion (79%). In fact, 92.5% consumed high-fat products, 75.12% red meats, 56% sweet products, and 43.12% full-fat dairy products. On the other hand, their consumption of beneficial products was below the average indicated. Or, 72.37% of this population have a water intake of less than 1.5L/day, more than a third (38%) don't eat fish, only 43% eat enough cereals and 36% enough fruit and vegetables a day. As a result, the degree of adherence to the Mediterranean diet is characterized by low adherence in more than half 52.37% versus only 47.63% who strongly adhere to the traditional Mediterranean diet. Factors responsible for low adherence were gender p<0.001, residence environment U/R. The study reveals a dietary imbalance in this community, known for its agricultural and maritime wealth. Certain food products are consumed in quantities above or below daily requirements. An overwhelming majority of 47% of the population exhibits a robust compliance with the MD. Furthermore, it was observed that 53% of the subjects studied did not follow this diet, which could be a determining factor in the onset and development of chronic diseases in future generations.